Development of interactive manipulative motion learning media using adobe animate for elementary school students - Lanos, Muhsana El Cintami; Handyani, Widya; Manullang, Jujur Gunawan; Winartiningsih, Anes; Festiawan, Rifqi (Jurnal Keolahragaan, 2024)
Over the past few years, there has been a growing recognition of the importance of integrating technology into educational practices to engage students more effectively. Traditional PE methods and limited resources have hindered effective learning, necessitating new approaches. This research aimed to develop innovative, interactive learning media based on adobe animate to enhance elementary students' learning outcomes in manipulative movement skills"”a crucial component of Physical Education (PE) that fosters physical, social, emotional, and cognitive development. Utilizing the research and development (R&D) method with Borg and Gall's ten-stage model, the study involved experts and participants from five elementary schools in Purwokerto City. Following a structured process of preliminary study, planning, development, field trials, product revisions, and large-scale testing, data were analyzed using SPSS software. Expert evaluations rated the media and material highly (91.25% and 87.50%, respectively), indicating strong acceptance and usability. Field trials showed increased student motivation and engagement, demonstrating the effectiveness of the interactive approach. Large-scale trials confirmed significant improvements in learning outcomes, with interactive media exhibiting greater efficacy compared to conventional methods. The paired sample t-tests revealed a statistically significant increase in learning outcomes, where Group A (utilizing interactive media) achieved a p-value of 0.001, whereas Group B (employing traditional methods) obtained a p-value of 0.040. The findings emphasize the critical role of incorporating innovative technologies like Adobe Animate in PE programs, offering a model for developing impactful learning media across diverse educational settings. Moreover, they stress the necessity for ongoing adaptation and feedback integration to sustain media relevance and effectiveness over time. Future research could investigate the long-term impacts of interactive media on varied subjects and learning environments, as well as explore possibilities for customizing instructional materials based on individual student needs.